Computer-Assisted Language Learning (CALL) in ESL Classrooms in India: Students’ perspective - Nathir Ghafar, Zanyar; Farheen ANJUM; Bareq Raad RAHEEM (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
improving learning outcomes. Computer-Assisted Language Learning (CALL) offers potential to enhance English as a Second Language (ESL) instruction, particularly in developing nations like India. Nonetheless, ESL learners often face challenges related to motivation, infrastructure, and pedagogical integration despite the growing technological accessibility. This study explores CALL effectiveness in Indian tertiary-level ESL classrooms, focusing on its impact on student engagement and language proficiency. A quantitative research was designed and the data was collected from 80 students in English departments through a structured questionnaire. The study assessed students’ perceptions of CALL. The authors analyzed benefits and challenges of CALL using descriptive statistics. The obtained data indicated students as generally benefitting from CALL. The participants mentioned increased motivation, language skills, and access to diverse learning materials. However, we found that the optimum CALL implementation was hindered by several barriers. Key barriers were unreliable internet access, technical difficulties, limited teacher training, and insufficient resources. The present study highlights the need for targeted interventions, including infrastructure development, teacher training programs, and institutional support, to maximize CALL’s potential. Removing these barriers can foster more effective and engaging language learning experiences rendering CALL as a transformative tool in ESL education. The findings contribute to ongoing discussions on digital learning in ESL education and provide actionable recommendations for educators and policymakers seeking to enhance language instruction through technology.